Potential application of hybrid reverse electrodialysis (RED)-forward osmosis (FO) system to fertilizer-producing industrial plant for efficient water reuse - Tasneem, Elmakki (2023)
This study presents an experimental investigation and a parametric analysis of the applicability of agricultural fertigation and power generation using a reverse electrodialysis-forward osmosis (RED-FO) hybrid system, with a water stream discharged from a fertilizer-producing plant. The results of this study demonstrated the possibility of achieving high salinity power generation from the RED system utilizing high-salinity brine and low-salinity ammonia solution that simulates reverse osmosis (RO) brine and wastewater streams released by the fertilizer-producing industry. The feasibility of stream dilution for fertigation application is demonstrated when the resulting moderately saline RED effluent is introduced into the FO process as a draw solution. The effect of external load addition, flow velocities variation, and concentration changes of the working solutions on the overall stack internal resistance and, thereby, RED performance was evaluated. As such, the lowest internal resistance converged to a threshold value of 4.03 Ω, giving the highest gross power density of 2.17 W/m2 when a flow velocity of 1.18 cm/s, 10 Ω external load, and 0.015 M (NH4)2SO4/1 M NaCl solution pair were utilized. In addition, the effect of the number of ion exchange membrane pairs and wastewater stream recycling was studied and optimized to amplify the osmotically generated power. As a result, the most consistent power generation was achieved when using 20 pairs of membrane cells in a single-pass flow mode operation. The applicability of the RED effluent to a subsequent FO system as a draw solution (DS) was investigated, showing a dilution rate (17 %) and a conductivity (1–2 mS/cm of DS) suitable for agricultural fertigation applications.